GAMBARAN KEPATUHAN PENGOBATAN ARV (ANTIRETROVIRAL) (STUDI PADA WANITA PEKERJA SEKS (WPS) POSITIF HIV/AIDS DI KABUPATEN BATANG) - Khairunnisa Khairunnisa; Lintang Dian Saraswati; Mateus Sakundarno Adi; Ari Udiyono (Jurnal Kesehatan Masyarakat (Undip), 2017)
Antiretroviral (ARV) treatment means treating HIV infection with several medication. Obedience of ARV (antiretroviral) treatment is one of the factor to prolong life of the people with HIV AIDS. The purpose of this research was to describe the obedience of ARV treatment in women sex workers in Batang Regency. This was an observational descriptive study with cross sectional design. Total of the respondents were 82 people. In this research, all the population were becoming samples. The results showed that 32,9% respondents were obedient in ARV treatment, 71,9% respondents were not obedient in ARV treatment. The 62,2% respondents who were not obedient in ARV treatment were graduated from Junior High School., 72,9% respondents with income of Rp 1.500.000 were not obedient, 63,4% respondents who had good knowledge were not obedient, 68,2% respondents with good treatment attitude were not obedient, 66,1% respondents who had support from family were not obedient, 67,9% respondents who had good support from health officer or LSM were not obedient, 63,3% respondents with good service access were not obedient.The interview results showed that obedience of ARV treatment were detained by drug side effects and the fear of discrimination from the people around them.